Diversity of fungal endophytes in cymodocea rotundata and halophila ovalis in Nueva Valencia, Guimaras. - Ladores, Jeric Prince M. (2019.)
Majority of fungal endophyte studies are limited to terrestrial hosts such as medicinal plants and mangroves. However, few studies in seagrasses have been done. Minimal studies have been done on marine-derived fungi specifically with algar and seagrasses. Endophytes may provide new information on host-microbe interactions and lead towards new novel sources of beneficial bioactive compounds as well as aid in the conservation of the marine ecosystem biodiversity. Thus, this study was conducted in order to isolate and identify endophytic fungi associated with leaf blades and rhizomes of Cymodocea rotundata and Halophila ovalis, seagrasses in Nueva, Valencia, Guimaras. Leaf and rhizome samples were collected from the field and processed in the laboratory within 24 hours. Leaf and rhizome segments were inoculated on Potato Dextrose Agar (PDA)-saltwater plates supplemented with penicillin-streptomycin antibiotic. Plates were incubated at 35 ± 2°C for two weeks and examined daily for fungal growth. Pure cultures were acquired, and the identification of these isolates was based on available keys and monographs. A total of twenty-eight (28) species were collected from 104 samples of leaf blades and rhizomes. In general, Aspergillus flavus, white Mycelia sterilia and Aspergillus niger were the most frequently collected. The identified isolates are in the genra Aspergillus, Penicillium, Nodulisporium, and Mucor. The overall Shannon Index of Diversity was 2.82 and Dominance Index at 0.92. Fungal species collected from the rhizome samples across species at 23 from the total 28 species collected. Isolates collected from leaf samples across species, solely C. rotundata, and solely H. ovalis were 10, 17, and 17, respectively. Results show that there is evidence to suggest that fungal endophytes exhibit some form of specificity or tissue preference.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2019.
Keywords: Fungal Endophytes -- Nueva Valencia, Guimaras; Cymodocea rotundata; Halophila ovalis